2013
DOI: 10.1016/j.seppur.2012.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Formation of halogenated disinfection by-products during microfiltration and reverse osmosis treatment: Implications for water recycling

Abstract: A suite of 34 disinfection by-products (DBPs), including 8 halomethanes, 9 haloacetic acids, 6 haloacetonitriles, 6 haloaldehydes, 4 haloketones and the halonitromethane chloropicrin, were monitored in two microfiltration (MF) and reverse osmosis (RO) treatment plants as part of a larger study of chemical removal by MF/RO treatment for water recycling purposes. Both DBP detection frequency and concentration increased during treatment, and this was attributed to a chloramination step used to minimize RO membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…For example, in a recent study by Linge et al, full-scale plants in Perth, Australia, had several DBPs (THMs, dihalomethanes, HAAs, haloacetonitriles, and haloketones) in their MF/RO effluents that were not otherwise present in the incoming secondary wastewater or were initially present at significantly lower levels [162]. This is because MF/RO treatment typically includes chloramination of wastewater before MF to minimize RO membrane fouling [162,163], and thus, chloramination DBPs can form. The majority of DBPs are typically small, neutral molecules that show intermediate or poor RO rejection.…”
Section: Human Exposure To Cecs and Dbpsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a recent study by Linge et al, full-scale plants in Perth, Australia, had several DBPs (THMs, dihalomethanes, HAAs, haloacetonitriles, and haloketones) in their MF/RO effluents that were not otherwise present in the incoming secondary wastewater or were initially present at significantly lower levels [162]. This is because MF/RO treatment typically includes chloramination of wastewater before MF to minimize RO membrane fouling [162,163], and thus, chloramination DBPs can form. The majority of DBPs are typically small, neutral molecules that show intermediate or poor RO rejection.…”
Section: Human Exposure To Cecs and Dbpsmentioning
confidence: 99%
“…Plant residence time played an important role in the levels of DBPs observed, which resulted in greater frequency of detections at the full-scale plants vs. pilot-scale plants (which have smaller residence times). An unusual finding was the consistent detection of two dihalomethanes: dibromomethane and bromochloromethane, which are not routinely monitored and may be more toxicologically important than the regulated THMs [162]. It was suggested that DBP precursor removal should be optimized in secondary wastewater, such as implementing advanced biological treatment upstream of MF and RO processes.…”
Section: Human Exposure To Cecs and Dbpsmentioning
confidence: 99%
“…The dangers of HA in water manifest as a result of the use of disinfection processes such as chlorination. HA combines with disinfectants to form disinfection by-products (DBPs), such as trihalomethanes, halonitromethanes, haloacetonitriles, haloamides, halofuranones, iodo-acids and others, which are known to be carcinogenic and have the potential of causing adverse effects to human life (Fan et al, 2014;Hu et al, 2016;Jian et al, 2016;Kim et al, 2015;Linge et al, 2013;Xue et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Disinfectants/Disinfection Byproducts Rule established a maximum contaminant level (MCL) of 60 mg/L for the sum of five HAAs (HAA5 ¼ MCAA þ MBAA þ DCAA þ DBAA þ TCAA) under the Stage I (Pontinus, 1999). Biodegradation and reverse osmosis are used to remove HAAs from chlorinated water (Linge et al, 2013;McRae et al, 2004). The reverse osmosis treatment may generate a polluted waste that should be treated (Linge et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradation and reverse osmosis are used to remove HAAs from chlorinated water (Linge et al, 2013;McRae et al, 2004). The reverse osmosis treatment may generate a polluted waste that should be treated (Linge et al, 2013). Biodegradation may cause bacterial contamination in the treated water (McRae et al, 2004).…”
Section: Introductionmentioning
confidence: 99%